(untitled) (International Journal of Architecture and Urbanism, 2023)
Improper seismic design of buildings can lead to collapse and severe damage due to natural and unpredictable earthquake loads. Based on a comprehensive analysis of the effect of the quantity of reinforcement of the frame to the plastic hinge formation of the building at wall frame buildings, this paper proposes a rational seismic design method for the wall frame building by means of the reinforcement control method to protect the lives and property of the people and ensure the seismic stability of the building.